Spatio-temporal changes of ecological vulnerability across the Qinghai-Tibetan Plateau - Mu Xia (Elsevier, 2021)
The Qinghai-Tibetan Plateau (QTP) has the most fragile ecosystems in the world. Over the past decades, QTP is suffering from increasing external pressures of climate change, human activities, and natural hazards, thus ecological vulnerability assessment is crucial for its sustainable development. This study proposes an objective and automatic framework to assess the ecological vulnerability in the QTP under the threats of mountain hazards, ecosystem degradation and human economic activities and then analyze its spatio-temporal patterns from 2000 to 2015. An ecological vulnerability index (EVI) is established by integrating natural and anthropic factors based on sub-systems of land resources, hydro-meteorology, topography, and social economics. Seventeen indicators are selected to reflect ecological conditions and their weights are determined by principle component analysis and entropy weighting methods. Then, the EVI values are automatically categorized into five vulnerability levels of potential, light, moderate, heavy, and very heavy to illustrate their spatio-temporal patterns across the QTP. Results indicated that spatial distributions of EVI across the QTP exhibited similar patterns during the study period at an overall heavy level. Among all the indicators, vegetation was the dominant driver for ecological vulnerability. Based on trend analyses during the study period, approximately 10.43% of the QTP, mainly distributed in Tibet Autonomous Region, experienced significant increase in ecological vulnerability, while 7.38%, mainly distributed in Qinghai Province, experienced significant ecological vulnerability declination. However, more detailed analyses showed that after the implementation of several ecological protection programs, the increasing trend of ecological vulnerability was eased and more regions experienced significantly decreasing vulnerability. This indicated the ecological restoration projects conducted by the government were efficient in reducing ecological vulnerability.